Sustainable Crop Plants Protection: Implications for Pest and Disease Control - Olivares Campos, Barlin Orlando; Araya-Alman, Miguel; Marys, Edgloris E. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint, titled "Sustainable Crop Plants Protection: Implications for Pest and Disease Control", has become of scientific interest again for a reason: to continue its mission of advancing the science and practice of sustainable agriculture. This Special Issue delves into the multifaceted world of crop protection, exploring innovative approaches, technologies, and solutions that are pivotal for the future of agriculture. Our objectives remain as relevant today as they were when the first call went out for the Special Issue of sustainability, to shed light on sustainable pest and disease control strategies, foster scientific collaboration, and provide a platform for sharing knowledge that can transform agriculture for the better.